Are age and radiographic features effective on orthodontic alignment of palatally impacted maxillary canines? a retrospective study - Seda Koçyiğit; Abdullah Alper Oz; Burcu Baş; Nursel Arıcı; Selçuk Karahan (European Oral Research)
PurposeThe purpose of the study was to evaluate the effects of age and radiographic parameters on success of orthodontic alignment of impacted maxillary canines.Materials and MethodsThe retrospective records of 50 patients (mean age 20.44 years) who had impacted maxillary canines in palatal position were included. The patients was requiring surgical exposure and mechanical orthodontic treatment were divided into two groups as adolescent (age≤18; n=24) and adult (age>18; n=26). In both groups, the treatment time and success were evaluated clinically and radiographically.ResultsFifty patients between the ages of 13 to 42 (12 males and 38 females) with palatally impacted canines were treated with combined surgical-orthodontic approach. Forty-seven teeth (94%) had reacted to surgical exposure and orthodontic alignment within 16 to 36 months with a mean of 24.81 months. Three of the impacted canines (6%) were surgically removed because no movement was observed following 10 months of traction forces.ConclusionThe distance of the canine tip to the occlusal plane on the lateral cephalometric radiographs have found to be related with the total orthodontic treatment time. Neither the age of the patient nor other clinic and radiographic parameters had influence on the treatment results of alignment of maxillary canines following surgical exposure.